DOI: 10.1159/000423895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin-Converting Enzyme and Calcium Channel Inhibition on Progression of IgA Nephropathy

Abstract: Recent attention has been focused on the role of glomerular haemodynamic alterations in the progression of IgA nephropathy (IgAN) and other forms of chronic glomerulonephritis. In particular, glomerular capillary hypertension has been suggested to play an important role in this process [I]. Angiotensin-converting enzyme inhibitors (ACEI) preferentially dilate the efferent glomerular arteriole thereby lowering glomerular capillary pressure and studies in experimental animals [2] and man [3] have now documented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…It has been suggested that AngII-induced mesangial cell contraction with efferent arteriolar vasoconstriction initiates intraglomerular hypertension and may eventually lead to enhanced matrix formation and renal fibrosis after increased synthesis of TGF-␤ (12). The beneficial effects of either angiotensin-converting enzyme (ACE) inhibitors (ACEI) or AngII subtype 1 (AT 1 ) receptor antagonists on proteinuria and creatinine clearance (independent of BP reduction) highlight the importance of this system in IgAN (13,14). In this study, we explore whether pIgA1 isolated from patients with IgAN exerts any stimulatory effect on the RAS of mesangial cells, resulting in increased synthesis of TGF-␤.…”
mentioning
confidence: 99%
“…It has been suggested that AngII-induced mesangial cell contraction with efferent arteriolar vasoconstriction initiates intraglomerular hypertension and may eventually lead to enhanced matrix formation and renal fibrosis after increased synthesis of TGF-␤ (12). The beneficial effects of either angiotensin-converting enzyme (ACE) inhibitors (ACEI) or AngII subtype 1 (AT 1 ) receptor antagonists on proteinuria and creatinine clearance (independent of BP reduction) highlight the importance of this system in IgAN (13,14). In this study, we explore whether pIgA1 isolated from patients with IgAN exerts any stimulatory effect on the RAS of mesangial cells, resulting in increased synthesis of TGF-␤.…”
mentioning
confidence: 99%
“…inhibition of cell proliferation, reduction of intraglomerular pressure) [24][25][26][27]. Therefore, in the treatment of hypertension developing in chronic GN, an ACEI should be the drug of choice, which may have to be supplemented with a calcium channel blocker, provided our choice is not influenced by other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the prognostic values in histopathological alterations, high blood pressure is an important negative prognostic marker in IgA nephropathy and should be treated early in the course (21). Conversly, antihypertensive treatment ameliorates the progression of renal dysfunction in patients with IgA nephropathy (22). Cattran et al showeda retrospective analysis comparingangiotensin-converting enzymeinhibitors in 27 patients to other treatment in 55 and no treatment in 33 patients (23).…”
Section: Aggressive Blood Pressure Reduction In Patients With Chronicmentioning
confidence: 99%